Citra Diri Digital Pemain Roblox melalui Kustomisasi Avatar: Studi Fenomenologi pada Remaja Indonesia - Nuraini Fazilatun Nisa; Asep Soegiarto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze how Indonesian adolescents represent their self-image through avatar customization in Roblox. This research uses a qualitative approach with a phenomenological method to explore the subjective experiences of players in constructing their digital identities. Data were collected through in-depth interviews with adolescent Roblox users who actively customize their avatars and interact within virtual spaces. The findings show that avatar customization is not merely a visual display, but a meaningful process of self-representation. Through avatars, adolescents express how they perceive themselves as well as how they want to be perceived by others. This process involves impression management, where the avatar functions as the “front stage,” while personal motivations and considerations remain in the “backstage.”. Furthermore, Roblox does not only function as an entertainment platform, but also as a social space where identity is formed, negotiated, and expressed. This study is expected to contribute to digital communication studies, particularly in understanding the formation of digital self-image and identity construction among adolescents in virtual spaces. These findings also highlight the importance of virtual environments in shaping contemporary youth identity.